AB0251 Female Reproductive Factors and the Development of Anti-Citrullinated Protein Antibodies in Women at Risk of Rheumatoid Arthritis. (9th June 2015) - Alpizar-Rodriguez, D.; Mueller, R.B.; Möller, B.; Dudler, J.; Ciurea, A.; Zufferey, P.; Kyburz, D.; Walker, U.A.; Von Mühlenen, I.; Cornelis, F.; Bas, S.; Roux-Lombard, P.; et al.
Abstract : Background: The etiopathogenesis of rheumatoid arthritis (RA) is viewed as a multi-step process whereby environmental factors induce pathologic activation of the immune system that eventually leads to clinical onset of RA in genetically susceptible individuals. Systemic autoimmunity associated with RA is one of the phases preceding the development of the disease. The role of female hormonal factors is controversial and their relation in the transition to systemic autoimmunity has not been studied. Recently, observational studies have suggested differences in the role of female reproductive factors between anti-citrullinated protein antibodies (ACPA) negative and positive RA. Objectives: To analyze the association between female reproductive factors and the development of systemic autoimmunity associated with RA. Methods: This is a prospective cohort study of first degree relatives (FDRs) of patients with established RA. Only individuals without clinical evidence of RA are enrolled and followed-up yearly. We included in this analysis only female participants with available ACPA status (anti-CCP 2.0 or 3.1) and full information on reproductive factors. The outcome of interest was the presence of ACPA. The predictor of interest was the cumulative lifetime estrogen (CLE) exposure as previously described (1). This composite score integrates a history of menarche ≤10 years, 3 or more pregnancies, hysterectomy, hormonal contraceptive or replacement therapy and age at menopause ≥53 years. Based on the CLE score, women were categorized as being low, moderate or high estrogen exposed. We used logistic regression to analyze univariate and multivariate associations between ACPA positive status, CLE exposure and other specific reproductive factors. Results: A total of 583 women FDRs were analyzed, of which 93 (16%) were ACPA-positive. Characteristics were balanced between ACPA positive and negative FDRs with a mean age of 48.3 and 44.9 years and heavy tobacco smoking (>10 pack-years) in 45 and 46% respectively. Positive shared epitope (SE) in 8 and 10% and positive rheumatoid factor in 17% of subjects in both groups. In a multivariate adjusted analysis, low CLE exposure was associated with ACPA positivity (OR 1.88, p=0.03). High CLE exposure was also numerically associated with an increased risk of ACPA (OR 1.57, p=0.36), even though not significantly. We found no significant association between ACPA positivity and SE, ever smoking, obesity, breastfeeding or postmenopausal status. Conclusions: In women at increased risk of RA, the development of ACPAs was found to be associated with low lifetime exposure to estrogens, however high lifetime estrogen exposure also tended to increase the risk of ACPAs positivity, suggesting a non-linear association between estrogenic exposure and the development of ACPAs. We plan to replicate these findings in a separate cohort. If this non-linear association was confirmed it could explain some discordant findings in the literature. References: Gatto NM et al. Parkinsonism Relat Disord 2014; 20(11):1149-56. Disclosure of Interest: None declared